ANALISIS HASIL BELAJAR SISWA MELALUI PEMBELAJARAN MENGGUNAKAN LKS BERBASIS POE (PREDICT, OBSERVE, EXPLAIN) BERBANTU PHET SIMULATION - Nur Istiqomah; Bambang Supriadi; Lailatul Nuraini (FKIP Universitas Jember, 2019)
Abstract This research was carried out to improve students' learning outcomes by using students' worksheet based on POE (Predict, Observe, Explain).This research was conducted in class X of SMA Muhammadiyah 3 Jember in the 2019/2020 school acadenic year. This research used experimental research methods. The instruments used in this study were lesson plan, syllabus, students' worksheet based on POE (Predict, Observe, Explain), and post-test question. After analyzing it by comparing with the results of the daily chapter of the previous chapter, it was found that the test scores using LKS based on POE (Predict, Observe, Explain) were higher compared to conventional learning . Thus it can be concluded that class given treatment in the form of learning by using students' worksheet based on POE (Predict, Observe, Explain) has a significant effect on the students' learning outcomes compared to class with conventional learning. Keywords : Students Worksheet, POE (Predict, Observe, Explain), students' learning outcomes